MSLN Correlates With Immune Infiltration and Chemoresistance as a Prognostic Biomarker in Ovarian Cancer - Li, Yike; Tian, Wanjia; Zhang, Hong; Zhang, Zhijian; Zhao, Qinghe; Chang, Lei; Lei, Ningjing; Zhang, Weiwei (Frontiers in Oncology, 2022)
Mesothelin (MSLN) is a glycoprotein with various expression degrees in different tumors including mesothelioma, ovarian cancer, pancreatic cancer, etc. MSLN is considered to play an important role in cell survival, proliferation, and tumor progression. Although the expression of MSLN in tumors makes it a potential therapeutic target, its mechanism of action is still unclear, especially its correlation with immune cells infiltration in the tumor microenvironment has not been investigated. In this study, we detected the overexpression of MSLN in ovarian cancer using database analysis and tissue-array staining. We further evaluated the diagnostic value of MSLN and found it was associated with poor overall survival in ovarian cancer. In addition, the high expression of MSLN was significantly related to the immune-related genes and chemoresistant genes. We confirmed the overexpression of MSLN in the chemoresistant ovarian cancer cell lines. Our research suggests that MSLN participates in a variety of pathways related to the suppression of immune activation and promotion of chemoresistance, leading to a poor prognosis in ovarian cancer.